2021
DOI: 10.1016/j.jiac.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Estimated effectiveness of school closure and voluntary event cancellation as COVID-19 countermeasures in Japan

Abstract: Background As countermeasures against the COVID-19 outbreak, sports and entertainment events were canceled (VEC) in Japan for two weeks from 26 February through 13 March. Moreover, most schools were closed (SC). Objective For this study, we estimated the basic reproduction number (R 0 ) and SC and VEC effects. Method After constructing a susceptible–infected–recovered model with three age classes, we used data of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 14 publications
0
28
0
2
Order By: Relevance
“…The following procedure was similar to that used for our earlier research [8,9]. We estimated the onset date of patients for whom onset dates were not reported as follows:…”
Section: The Number Of Symptomatic Patients Reported By the Ministry mentioning
confidence: 99%
“…The following procedure was similar to that used for our earlier research [8,9]. We estimated the onset date of patients for whom onset dates were not reported as follows:…”
Section: The Number Of Symptomatic Patients Reported By the Ministry mentioning
confidence: 99%
“…Similar analyses by other researchers reinforce that varying adoption rates of peer-to-peer contact tracing apps can influence the trajectory of the pandemic [ 17 , 29 ]. By employing the simulation model described in [ 30 ], we estimated how the rate of participation would affect the trajectory of the COVID-19 pandemic in Japan ( Figure 5 ). The model evaluates scenarios in which the epidemic is established and countermeasures such as contact tracing are employed to control the spread of COVID-19; it can be observed how the trend of the effective reproduction number (R t ) and thus of the outbreak would dynamically change.…”
Section: Statistical Analysis and Simulation Resultsmentioning
confidence: 99%
“…Prior research identified that when R t , which is defined as the average number of secondary cases generated by a single infectious case, decreases to less than one (ie, R t <1), transmission of the disease will stop and the pandemic will ultimately be contained [ 22 - 24 ]. The simulation was calibrated to the demographic attributes in Japan [ 14 , 22 , 25 - 27 , 29 ], the basic reproduction number (ie, 2.56) found for Japan [ 30 ], and the ratios of symptomatic patients in the report by the National Institute of Infectious Diseases in Japan [ 31 ]. The assumptions for the simulation are as follows: (1) the population can freely choose to opt in or opt out from COCOA; (2) there are no delays in data sharing; and (3) all the populations in households, schools, workplaces, and other scenarios can be successfully digitally traced.…”
Section: Statistical Analysis and Simulation Resultsmentioning
confidence: 99%
“…Kedua, para pemimpin akademik harus mendistribusikan tanggung jawab kepemimpinan ke jaringan tim di seluruh organisasi untuk meningkatkan kualitas keputusan yang dibuat dalam penyelesaian krisis. Ketiga, para pemimpin harus berkomunikasi dengan jelas dan sering kepada semua pemangku kepentingan melalui berbagai saluran komunikasi (Fernandez & Shaw, 2020b;Kurita, Sugawara, & Ohkusa, 2021).…”
Section: Pendahuluanunclassified